African strains of Zika virus resist ISG-mediated restriction. - Inès Bribes; Jim Zoladek; Marion Cannac; Sara Salinas; Sam J Wilson; Sébastien Nisole (PLoS Neglected Tropical Diseases)
Zika virus (ZIKV) is a neurotropic Orthoflavivirus transmitted by mosquito vectors, which has evolved into two lineages, namely African and Asian. ZIKV from the Asian lineage has been responsible for epidemics in the Pacific and the Americas, the largest of which occurred in Brazil in 2015 and was associated with severe neurological disorders, including cases of microcephaly and other congenital fetal malformations. Although never implicated in human epidemics, African strains exhibit faster replication, higher virus production, and greater virulence in animal models compared to their Asian counterparts. A key feature that may account for the better fitness of African ZIKV strains compared to Asian ones is the fact that they are more resistant to interferon (IFN). IFN response is a major host defense mechanism against viral infections, which culminates in the induction of hundreds of IFN-induced genes (ISGs) whose products inhibit viral replication. By screening an array of ISGs known for their antiviral activity, we show that African ZIKV strains are globally more resistant than their Asian counterparts to ISG-mediated restriction. In particular, SHFL, RTP4 and IFI6, which were the three most active ISGs against Asian viruses, had little or no effect on the replication of African ZIKV strains. These observations therefore suggest that if African strains are more resistant to the antiviral effect of IFN than Asian strains, this is not because they have greater capacity to inhibit IFN signaling, but rather because they are able to escape ISG-mediated restriction. Our results provide an explanation as to why viruses of African origin spread more rapidly and efficiently in vitro than their Asian counterparts as repeatedly demonstrated. However, it remains unclear why, despite their greater virulence and resistance to cellular antiviral defenses, ZIKV strains of the African lineage have never been identified in large-scale epidemics.